Ideal Concept In The Implementation Of Legal Philosophy In The Perspective Of Sociological Jurisprudence In Indonesia - Nuraharja Adi Partha, Putu Gde; Lia Puspita, Putu; Rato, Dominikus (Journal of Law, Politic and Humanities, 2024)
The philosophical thought of law in a new paradigm that identifies reason as the primary source of law, emphasizing rationality and humanism in the development of modern law. This emphasizes the inseparability of law from social life and the formation of legal values within communities, shaping norms that guide social behavior and reflect the essence of law. The discussion extends to studying indigenous communities, especially in Kalimantan, where customary law arises from experiential actions, recognized and regulated by the Indonesian constitution, acknowledging the existence of written and unwritten laws within the framework of customary law. The research method used is normative juridical with a conceptual approach based on these issues. The research findings indicate that the conception of legal philosophy studies related to Sociological Jurisprudence becomes important because it enables law to become an instrument that promotes social justice and equality, recognizing that law must reflect respected social values and be executed within society based on the thoughts of Hugo Grotius regarding justice, equality, and human rights, grounded in rationality and humanism, emphasizing the need to treat individuals with respect and consider the welfare of society. The implementation of Hugo Grotius's thought in Indonesia has made a significant contribution to a paradigm shift in legal construction, particularly related to Sociological Jurisprudence. Grotius emphasizes the importance of rational law that does not solely rely on dogma or religious beliefs. His views on justice based on reason and human rights as an integral part of natural law have shaped a modern legal perspective that prioritizes justice and equality. Grotius's thoughts are highly relevant, especially in efforts to build a fair legal system based on morality.